Heart failure epidemiology and treatment in primary care: a retrospective cross‐sectional study. (7th November 2020) - Rachamin, Yael; Meier, Rahel; Rosemann, Thomas; Flammer, Andreas J.; Chmiel, Corinne
Abstract: Aims: Heart failure is one of the leading causes of morbidity and mortality worldwide, but little is known on heart failure epidemiology and treatment in primary care. This study described patients with heart failure treated by general practitioners, with focus on drug prescriptions and especially on the only specific treatment for heart failure with reduced ejection fraction, namely sacubitril/valsartan. Methods and results: This was a retrospective cross‐sectional study using data from an electronic medical record database of Swiss general practitioners from 2016 to 2019. Multilevel logistic regression was used to find determinants of sacubitril/valsartan prescription; odds ratios (ORs) and 95% confidence intervals (CIs) were reported. We identified 1288 heart failure patients (48.5% women; age: median 85 years, interquartile range 77–90 years) by means of diagnosis code, representing 0.5% of patients consulting a general practitioner during the observation period. About 73.6% received a renin–angiotensin–aldosterone system inhibitor, 67.8% a beta‐blocker, 34.6% a calcium channel blocker, 86.1% a diuretic, and 40.1% another cardiac drug. Sacubitril/valsartan was prescribed in 6% predominantly male patients (OR 2.10, CI 1.25–3.84), of younger age (OR 0.59 per increase in 10 years, CI 0.49–0.71), with diabetes mellitus (OR 1.76, CI 1.07–2.90). The recommended starting dose for sacubitril/valsartan was achieved in 67.1% and the target dose in 28.6% of patients. Conclusions: Prevalence of heart failure among patients treated by general practitioners was low. Considering the disease burden and association with multimorbidity, awareness of heart failure in primary care should be increased, with the aim to optimize heart failure therapy.